Biosynthesis of Indol-3-yl-acetyl-myo-inositol Arabinoside in Kernels of Zea mays L. - Corcuera, Luis J. (1982)
Extracts of immature kernels of Zea mays L. catalyzed the synthesis of indol-3-yl-acetyl-myo-inositol arabinoside from indol-3-yl-acetyl-myo-inositol and UDP-[U-(14)C]xylose. The product contained radioactivity which upon hydrolysis with trifluoroacetic acid cochromatographed with arabinose and not xylose. The amount of product from the reaction was proportional to the amount of indol-3-yl-acetyl-myo-inositol added, and the product was positive to Ehmann's reagent for indoles. In addition, the product and authentic indol-3-yl-acetyl-myo-inositol arabinoside had the same R(F) or retention time in three chromatographic systems. By analogy to the wheat germ system, it is proposed that a UDP-d-xylose 4-epimerase is present in immature kernels of maize and that this enzyme catalyzes the conversion of UDP-d-xylose to UDP-l-arabinose, the probable sugar donor to indol-3-yl-acetyl-myo-inositol. The present data demonstrates the presence of a previously undescribed enzyme, UDP-arabinose:indol-3-yl-acetyl-myo-inositol arabinosyl transferase in maize kernels. This work together with our prior studies provides a pathway for the biosynthesis of all the low molecular weight esters of indol-3-yl-acetic acid in maize kernels.